THE CHOICE OF THE SOURCE OF LASER RADIATION FOR THE PURPOSES OF INDUSTRIAL PARTS CLEANING AIRCRAFT EQUIPMENT - Планковський, С. І.; Цегельник, Є. В.; Головін, І. І.; Мельничук, П. І. (Science-based technologies, 2014)
This article presents the experimental investigation results on identifying possibility of using laser light for industrial purposes of cleaning construction elements surfaces on aircraft and land engineering objects. Considered were three cases of laser light usage. The first case concerns with removal of paint and coatings from aircraft surface. The second case deals with surface corrosion trace removal and operating carbon deposit removal from surface of foil turbine. The third case considered removal of high-temperature corrosion products from piston surface. The laser sources were detected which allows us to conduct the aforementioned operations. The analysis of experimental findings was given. The image of possible laser source for industrial laser cleaning was formed.